In vivo immunotoxicity of perfluorooctane sulfonate in BALB/c mice: Identification of T-cell receptor and calcium-mediated signaling pathway disruption through gene expression profiling of the spleen. (5th October 2015) - Lv, Qi-Yan; Wan, Bin; Guo, Liang-Hong; Yang, Yu; Ren, Xiao-Min; Zhang, Hui
Abstract: Perfluorooctane sulfonate (PFOS) is a persistent organic pollutant that is used worldwide and is continuously being detected in biota and the environment, thus presenting potential threats to the ecosystem and human health. Although PFOS is highly immunotoxic, its underlying molecular mechanisms remain largely unknown. The present study examined PFOS-induced immunotoxicity in the mouse spleen and explored its underlying mechanisms by gene expression profiling. Oral exposure of male BALB/c mice for three weeks followed by one-week recovery showed that a 10 mg/kg/day PFOS exposure damaged the splenic architecture, inhibited T-cell proliferation in response to mitogen, and increased the percentages of T helper (CD3 + CD4 + ) and cytotoxic T (CD3 + CD8 + ) cells, despite the decrease in the absolute number of these cells. A delayed type of PFOS immunotoxicity was observed, which mainly occurred during the recovery period. Global gene expression profiling of mouse spleens and QRT-PCR analyses suggest that PFOS inhibited the expression of genes involved in cell cycle regulation and NRF2-mediated oxidative stress response, and upregulated those in TCR signaling, calcium signaling, and p38/MAPK signaling pathways. Western blot analysis confirmed that the expressions of CAMK4, THEMIS, and CD3G, which were involved in the upregulated pathways, were induced upon PFOS exposure. Acute PFOS exposure modulated calcium homoeostasis in splenocytes. These results indicate that PFOS exposure can activate TCR signaling and calcium ion influx, which provides a clue for the potential mechanism of PFOS immunotoxicity. The altered signaling pathways by PFOS treatment as revealed in the present study might facilitate in better understanding PFOS immunotoxicity and explain the association between immune disease and PFOS exposure. Graphical abstract: Highlights: PFOS altered spleen cell composition and inhibited T-cell mitogenic reaction. PFOS inhibited gene expression of cell cycle and NRF2-mediated pathways. PFOS modulated gene expression of p38 MAPK pathway. PFOS activated TCR-MHC-II mediated pathways. Acute PFOS exposure induced calcium influx of splenocytes.